Pengaruh Kesalehan Individual dan Sosial Terhadap Minat Belajar Pendidikan Agama Islam Pada Siswa Kelas VII SMP Negeri 12 Cilegon dan SMP Tunas Bangsa Cilegon - SOFIYATI; Wasehudin; Muhajir; Apud; Habudin (Fakultas Agama Islam, 2026)
The Influence of Individual and Social Piety on Interest in Learning Islamic Religious Education in Grade VII Students of SMP Negeri 12 Cilegon and SMP Tunas Bangsa Cilegon. The type of research used in this study is correlational research which aims to identify the relationship between two or more variables. In this study, the relationship between individual piety, social piety, and interest in learning Islamic Religious Education (PAI) was analyzed to determine the extent to which these variables are interrelated. The results of the study showed that there was a significant influence between the individual piety variable (X1) on the interest in learning Islamic Religious Education (PAI) in class VII students of SMP Negeri 12 Cilegon and SMP Tunas Bangsa Cilegon. This is evidenced by the regression equation, namely Y = ‎38.065 + 0.590X. Based on the hypothesis testing, the t-value was obtained = 3.369 with a significance value of 0.002 <0.05, there was also a significant influence between the social piety variable (X2) on the interest in learning Islamic Religious Education (PAI) in class VII students of SMP Negeri 12 Cilegon and SMP Tunas Bangsa Cilegon (Y). This is proven by the regression equation, namely Y = ‎10.570 + 0.897X. Based on the hypothesis testing, the t-value = 1.650 was obtained with a significance value of 0.000 <0.05, there is also a significant influence between individual piety (X1) and social piety (X2) with interest in learning Islamic Religious Education (Y) in class VII students of SMP Negeri 12 Cilegon and SMP Tunas Bangsa Cilegon. This is proven by the results of the multiple linear regression analysis test obtained an R2 value = 0.853 which is in a Very Strong influence. Keywords: Individual Piety, Social Piety, Learning Interest.